Emotional support at work: A key component for nurses' work engagement, their quality of care and their organizational citizenship behaviour. (2022) - Pohl, Sabine; Battistelli, Adalgisa; Djediat, Abdel; Andela, Marie
Abstract: Background: There is growing interest in the relationships between supervisor/co-worker support and nurses' perceived quality of care and organizational citizenship behaviours. However, few studies have investigated the effects of emotional support of supervisors and colleagues on the performance of nurses over time and the psychological mechanisms that underlie the above-mentioned relationships. Objective: The aim of our study was to better understand the process promoting nurses' perceived quality of care and organizational citizenship centred on helping others. To better understand these processes, we focused on the perceived emotional support originating from the supervisor and that from the co-workers and analysed to which extent they were, over time, related to quality of care and organizational citizenship through work engagement. Method: A two-wave design was used to collect the data. Survey data was gathered from 188 nurses from two hospitals in Algeria. Mediation analyses were carried out using structural equation modelling. Results: The results revealed that nurses' work engagement mediates the relationships between quality of care, organizational citizenship behaviour and supervisor and co-workers emotional support. Conclusion: Results underlined the importance of putting in place schedules to improve supervisor emotional support, co-worker emotional support and work engagement in order to improve quality of care.